Revitalization in a part of Jakarta kota historic area - Farayune Hajjar, Farayune Hajjar (2008)
The revitalization of Jakarta Historic area is a program to conserve the heritage architecture and environment. This program attempts to improve the area to become attractive place by creating new activities, providing public facilities and improving the accessible facilities. The aim of this study is to provide the guidelines of revitalization action and promote Jakarta Kota as public and tourism place, by proposed this area become an attractive place. This study focus on the people activity, historical building, public places and accessible facility, which will encourage the improvement and redevelopment of the study area. From the study, it proves that the historic area have a role in town development planning, also it can impact the characater and image of the town. Creating various activities in the study area is one of the aspect to improve the public facility. Finally, revival of the historic area need to be focused on as well as understanding the people activity and environmental facility.